HD-2D: routine high-dispersion two-dimensional NMR spectra at no extra cost. Issue 86 (2nd September 2016) - Aguilar, Juan A.; Belda, Raquel; Botana, Adolfo; Kenwright, Alan M.
Abstract : The synergic use of pure shift NMR techniques and compressive sensing (compressed NMR) allows the recording of two-dimensional NMR spectra with much higher dispersion (effective resolution) than can be achieved using conventional techniques. Abstract : The synergic use of pure shift NMR techniques and compressive sensing allows the recording of two-dimensional NMR spectra with much higher dispersion (effective resolution) than can be achieved using conventional techniques. This gain requires no additional hardware and no increase in experiment time. We show that this combination of techniques can be implemented routinely and illustrate the significant advantages that result, enabling analyses that would otherwise have been extremely problematic.